Tajwīd al-Tajrīd as Kemālpāshāzāde’s Critique and Reconstruction of Tajrīd: Study and Critical Edition - Ömer Mahir Alper; Yasin Apaydın (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
Kemālpāshāzāde Aḥmed Efendī (d. 940/1534), one of the most distinguished and prolific scholars and philosophers of the Ottoman era, presented systematic criticisms of some earlier foundational texts under the titles of “revision” (taghyīr), “correction” (ıṣlāḥ), and “refinement” (tajwīd). His critical project incorporated a solid criticism of these seminal and influential works in linguistic, rational, and traditional sciences, both in form and in content. He also included Naṣīr al-Dīn al-Ṭūsī’s (d. 672/1274) Tajrīd al-iʿtiqād in this project. In his Tajwīd, Kemālpāshāzāde rewrote this work and wrote a commentary upon it, namely, Sharḥ Tajwīd al-Tajrīd. His interest in Tajrīd was not limited to these two, for in addition to a separate commentary (Sharḥ al-Tajrīd) he also wrote superglosses on some glosses of Tajrīd, such as Ḥāshiya li-Ḥāshiyat al-Jalāl. So far, neither his general project nor these two works have attracted sufficient scholarly interest. In this article, we focus on Kemālpāshāzāde’s studies on Tajrīd and present a detailed study of Tajwīd, as well as – and for the first time – its critical edition based on all of the extant manuscript copies. Thus, the article is in four parts: The Ottoman Tajrīd Tradition: From Tajrīd to Tajwīd, Kemālpāshāzāde’s Studies on Tajrīd, Kemālpāshāzāde’s Critique on Tajrīd: Tajwīd al-Tajrīd,” and Tajwīd al-Tajrīd.